Pengembangan Tes Diagnostik Miskonsepsi Three-Tier Test pada Materi Hukum Newton - Roza, Media; Bulan, Sari (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
The purpose of this study was to develop a diagnostic test in the form of a Three-tier test to identify students' mis-conceptions in Newton's Law material. This research is a development study using the 4D model (Thiagarajan). Threer-tier test diagnostic test instrument format consists of 20 items. Item validation was obtained from the consideration of expert lecturers. The practicality test of the Diagnostic Test questions is given to physics educators and students of class X IPA SMAN 1 Sungai Beremas. The effectiveness test was carried out on 20 students of class X IPA 1 of SMAN 1 Sungai Beremas. The test results show that the developed diagnostic tests are valid with an average of 86,11, practicalÂ  with an average of 93 (educators) and 83 (students). Effectiveness can be seen from the analysis of misconceptions, namely students experiencing high mis-conceptions of 7 people (35%), moderate misconceptions of 8 people (40%), and low misconceptions of 5 people (25%). It seems that the diagnostic test developed is valid, practical and able to detect misconceptions in students.